NEWS FRAMINGS OF O GLOBO REGARDING CHINESE SOCIETY DURINGTHE COVID-19 PANDEMIC - Chen, Xuewu (Brazilian journalism research, 2025)
ABSTRACT - This study aims to explore the news framing of Chinese society during the COVID-19 pandemic in the Brazilian press, focusing on the daily newspaper O Globo. Based on the theory of news framing and the interpretative package analytical method, the investigation systematically analyzed news texts related to Chinese society, published by the newspaper between January 2020 and January 2023, within the pandemic context. The research findings revealed that the 111 analyzed journalistic articles were primarily structured around five frames: “severe pandemic”, “draconian measures”, “victory propaganda”, “Zero-Covid crisis”, and “strict censorship”. RESUMO – O presente estudo visa explorar os enquadramentos noticiosos sobre a sociedade chinesa durante a pandemia de covid-19 na imprensa brasileira, com foco no jornal diário O Globo. Baseando-se na teoria de enquadramento noticioso e no método analítico de pacote interpretativo, a investigação desenvolveu uma análise sistematizada dos textos noticiosos referentes à sociedade chinesa, publicados pelo jornal entre janeiro de 2020 e janeiro de 2023, no contexto pandêmico. Os resultados da pesquisa revelaram que as 111 matérias jornalísticas analisadas foram estruturadas principalmente em torno de cinco enquadramentos: “pandemia severa”, “medidas draconianas”, “propaganda da vitória”, “crise da ‘Covid zero’” e “censura rigorosa”. RESUMEN – El presente estudio tiene como objetivo explorar los encuadres noticiosos sobre la sociedad china durante la pandemia de covid-19 en la prensa brasileña, enfocándose en el periódico diario O Globo. Basándose en la teoría del encuadre noticioso y en el método analítico del paquete interpretativo, la investigación desarrolló un análisis sistemático de los textos noticiosos relativos a la sociedad china, publicados por el periódico entre enero de 2020 y enero de 2023, en el contexto pandémico. Los resultados del estudio revelaron que los 111 artículos periodísticos analizados estaban estructurados principalmente en torno a cinco encuadres: “pandemia severa”, “medidas draconianas”, “propaganda de la victoria”, “crisis del Covid cero” y “censura rigurosa”.